PHILOSOPHICAL INTERPRETATION OF SYMBOLISM OF ČIURLIONIS’ PAINTINGS - Bragina, Natalia; Stepanov, Vladislav (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The art of M.-K. Čiurlionis is unique and at the same time emblematic of the culture of the art nouveau period. A deep connection of his art to Lithuanian folklore was combined with his fascination with European philosophical trends of the turn of the 19th - 20th centuries. The aim of this article is to identify the cross-cutting themes (leitmotifs) in the artist’s works and, with the help of this, to reveal the philosophical basis of his works. The methods of research are the study and analysis of both individual Čiurlionis’ paintings and his artistic production in general, as well as the analysis of the literature devoted to his works. As the result, two groups of leitmotifs were identified in the Čiurlionis’ paintings: a) figurative themes; and b) non-figurative themes (up to complete abstraction). Analysis of the meanings of these themes and of their influence on the content of the paintings shows that concrete figurative images (themes of kings, bird, hand, and castle) are associated with Lithuanian folklore. Semi-abstract and abstract images (chaos, glance, gesture, and beauty) reveal the connection between the art of Čiurlionis and European philosophy, from Plato's ideas to Nietzscheism and mystic-visionary movements of the early 20th century. Revealing the philosophical basis of his paintings makes it possible to simultaneously review the artist’s entire work in the context of culture of art nouveau, understand this culture more deeply, and thus get a better understanding of some important phenomena of our time.